A poroelastic finite element model of the bone–cartilage unit to determine the effects of changes in permeability with osteoarthritis. Issue 3 (17th February 2017) - Stender, Michael E.; Regueiro, Richard A.; Ferguson, Virginia L.
Abstract: The changes experienced in synovial joints with osteoarthritis involve coupled chemical, biological, and mechanical processes. The aim of this study was to investigate the consequences of increasing permeability in articular cartilage (AC), calcified cartilage (CC), subchondral cortical bone (SCB), and subchondral trabecular bone (STB) as observed with osteoarthritis. Two poroelastic finite element models were developed using a depth-dependent anisotropic model of AC with strain-dependent permeability and poroelastic models of calcified tissues (CC, SCB, and STB). The first model simulated a bone-cartilage unit (BCU) in uniaxial unconfined compression, while the second model simulated spherical indentation of the AC surface. Results indicate that the permeability of AC is the primary determinant of the BCU's poromechanical response while the permeability of calcified tissues exerts no appreciable effect on the force-indentation response of the BCU. In spherical indentation simulations with osteoarthritic permeability properties, fluid velocities were larger in magnitude and distributed over a smaller area compared to normal tissues. In vivo, this phenomenon would likely lead to chondrocyte death, tissue remodeling, alterations in joint lubrication, and the progression of osteoarthritis. For osteoarthritic and normal tissue permeability values, fluid flow was predicted to occur across the osteochondral interface. These results help elucidate the consequences of increases in the permeability of the BCU that occur with osteoarthritis. Furthermore, this study may guide future treatments to counteract osteoarthritis.